Record values from a family of J-shaped distributions - Ahmad A. Zghoul (Statistica, 2013)
A family of J-shaped distributions has applications in life testing modeling. In this paper we study record values from this family of distributions. Based on lower records, recurrence relations and bounds as well as expressions for moments and product moments of record values are obtained, the maximum likelihood estimator of the shape parameter is derived and shown to be consistent, sufficient, complete and UMVU estimator. In addition, an application in reliability is given.